ChatGPT in Foreign Language Acquisition: a close ally or a distant concept for Macedonian university students? - Neshkovska, Silvana; Ivanovska, Lela; Trajkovska, Vesna; Kasaposka-Chadlovska, Milena (Respectus Philologicus, 2025)
ChatGPT has instigated a tectonic change in foreign language acquisition. The latest research shows that language learners use it to enhance their major language skills and boost their critical thinking, research activities, and exam preparation. Consequently, ChatGPT has significantly impacted all levels of education, particularly the tertiary level. This paper aims to showcase how Macedonian university students fare in employing ChatGPT for foreign language acquisition. The study examines whether they are sufficiently familiar with this chatbot and to what extent they use it in various language-learning contexts. It also explores students’ attitudes toward this novel tool for improving their language abilities. Insights are drawn from qualitative and quantitative analyses of data gathered via a tailor-made survey, which targeted Macedonian university students, the majority of whom took a foreign language course during the academic year 2023/2024. Even though only 180 university students from several higher education institutions in the RN Macedonia showed interest in the study, the findings reveal mixed student perceptions of ChatGPT’s effectiveness, with some recognising its benefits for writing, translation, grammar, and research, while others expressing scepticism, particularly regarding its role in generating high-quality writing ideas, improving speaking skills, and fostering critical thinking, and creativity.
Keywords: ChatGPT; AI; foreign language acquisition; higher education; Macedonia; students